Enhancing Technical and Soft Skills Through Robotics: The AraraBots 15-Year Case Study - Huang, Fabio; Caetano, Geffté L. De S.; Ottoni, Amanda; Bonetti, Gabriel R.; Andrade, Vinícius F. de; Falcão, Gabriel P.; Duenha, Liana (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
AraraBots is an extension initiative at the Faculty of Computing (FACOM/UFMS) focusing on robotics in education and competition. This paper presents a case study on the educational impact of the AraraBots project on computer science and computer engineering programs. The study analyzes how participation in AraraBots contributed to undergraduate students' technical and soft-skills development in Computer Science and Computer Engineering programs. A survey based on the Technology Acceptance Model (TAM) was conducted with 43 students who participated in the project between 2010 and 2025, revealing that students perceived significant improvements in technical skills, especially in programming, electronics, and project management. The analysis combined quantitative data (scores, percentages) with qualitative data (free-text responses). Additionally, the project fostered the development of soft skills such as teamwork, communication, and leadership. More than 80% of participants agreed that AraraBots filled gaps in the formal curriculum, providing practical experiences and interdisciplinary learning not covered in traditional courses. The findings highlight the role of robotics extension projects in enhancing academic engagement and professional preparation for students in computing fields.